Analysis of the Nutritional Content of Processed "TOKEN" for Pregnant Women with CED and Anemia - Iswari Pauzi; Yudha Anggit Jiwantoro; Ni Putu Karunia Ekayani; Ni Putu Dian Ayu Anggraeni (Jurnal Penelitian Pendidikan IPA, 2024)
Malnutrition in pregnant women often occurs in developing countries, including chronic energy deficiency (CED) and micronutrient deficiencies. The aim of this research is to analyze tuna and potato content using proximate analysis and acceptance testing using sensory testing. This type of research is Research and Development, namely the method used to produce certain products and increase the effectiveness of these products. This development research uses a quantitative approach in collecting and analyzing data on mixed tuna and potato. Addition tuna flour and potato flour with the highest average value of 3.84 (like) at the treatment level with the addition of tuna flour and potato flour (25:15%). With a nutrient content of 62.6% water, 4.7% ash content, 9.28% protein, 10.64% fat, 12.75% carbohydrates, and 13.2% Fe content. The high of nutrient, protein, and Fe can be used as a protein source for pregnant women With CED and Anemia